Chemical improvement of acid soils using calcareous amendments in rambutan cultivation in Honduras - Sosa-Rodrigues, Breno Augusto (2025)
Introduction. Soil acidity generates toxicity due to high aluminum concentrations and low macronutrients availability in rambutan (Nephelium lappaceum) cultivation, causing high production costs when corrected withsynthetic fertilizers and alkaline correctives. Objective. To improve soil acidity indicators through the use ofincreasing doses of two calcareous amendments in a rambutan crop located on the Caribbean coast of Honduras. Materials and methods. A trial was carried out between March and November 2023 under field conditions on aproducer’s farm in the municipality of San Francisco, Atlántida, Honduras. Increasing doses (0, 1, 2 and 3 Mg ha-1) of two types of calcareous amendments were evaluated: agricultural lime with 34.3 % Ca and 0.3 % Mg (CA), and calcite with 25.5 % Ca and 1.2 % Mg (CAL). A randomized complete block design with a 4 × 4 factorial arrangement and three repetitions was used, resulting in 16 treatments. Soil pH, exchangeable aluminum (Al3+), exchangeable acidity(Al3+ + H+), and H+ were measured on five occasions. Results. The individual use of each amendment stimulated the correction of the acidity indicators evaluated; the best dose was 3 Mg ha-1. Soil pH increased with higher doses of both liming materials, and the highest dose (6 Mg ha-1) combining both amendments showed the best response. Theconcentrations of H+, Al3+ and Al3+ + H+ decreased as liming doses increased, with a similar effect observed when using between 3 and 6 Mg ha-1. For most of the parameters analyzed, except H+, significant changes were recorded at the fourth sampling, six months after the lime application, with CA showing better results. Conclusions. Increasing doses of both calcareous amendments reduced soil acidity indicators in rambutan cultivation, with agricultural limeproviding better control.